Developing Tourism Products in an Emerging Ecotourism Village: Integrating ECOS and Doxey’s Irritation Index - Marciella Elyanta; Hasan Sobirin (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study was conducted due to the emerging condition of Harangan Girsang Paradise Ecotourism Village, which has recently been developed and still experiences low tourist visits, indicating the need for appropriate tourism product development strategies. This study aimed to evaluate the condition of tourism products, analyze community attitudes toward tourism development, and formulate appropriate development strategies. The study employed a descriptive qualitative and quantitative (mixed-methods) approach. Data were collected through observation, in-depth interviews with the 1 tourism village management, documentation, literature review, and questionnaires distributed to 18 community members and 18 visitors. The data were analyzed using qualitative analysis and descriptive statistics. The Ecotourism Opportunity Spectrum (ECOS) and Recreation Zone Index (RZI) were used to evaluate the conditions of tourism products, while Doxey’s Irritation Index was applied to analyze community attitudes. The findings indicated that tourism products were in the eco-generalist category, whereas community attitudes were at the euphoria stage, reflecting strong support for tourism development. Based on these findings, the recommended strategies include strengthening nature- and culture-based tourism products, improving human resource capacity, enhancing community participation, managing tourism impacts, and implementing gradual and sustainable promotion. These findings highlight the importance of integrating tourism product conditions and community attitudes in developing sustainable ecotourism destinations.